Formulation and Evaluation of Glipizide Tablets Utilizing Hibiscus Rosasinensis Leaves Mucilage - Sanjib Bahadur; Amit Roy; Pragya Baghel; Ananta Choudhury; Suman Saha; Ranabir Chanda (Indonesian Journal of Pharmacy, 2018)
This research work aims to develop glipizide tablets using Hibiscus rosasinensis leaves mucilage. The mucilage was extracted by using double distilled water and precipitated with ethanol. The precipitated mucilage was dried and grounded into powder. The tablet utilizing the mucilage as excipient was prepared by wet granulation method. The tablets were subjected to various tests. The evaluatory parameters of tablets were found to be within the limits as per United States Pharmacopoeia NF 24/19. FTIR spectrum reveals that there is no incompatibility between the ingredients used. Diabetes was induced in wistar albino rats using streptozotocin and effect of formulation on blood glucose level was determined. It was observed that the formulation could not sustain the release of glipizide. However, the glipizide release was retarded as the amount of mucilage was increased. It was observed that on the completion of antidiabetic study, the formulation could bring the blood glucose level to normal in group rats. However, the blood glucose level was still elevated in group administered with pure gliplizide. It can be concluded that HRM can be used to formulate glipizide tablets. The formulations with HRM shows better hypoglycemic activity and this may be attributed to antidiabetic activity of Hibiscus rosasinensis.